Reamed versus unreamed intramedullary nailing in the treatment of elderly pertrochanteric femoral fractures: evaluation of the systemic inflammatory response and organ dysfunction - Michele Bisaccia (International Journal of Surgery and Medicine, 2017)
Background: Currently, the most widely used technique of osteosynthesis in the treatment of proximal femur fractures is the intramedullary nailing and canal reaming. However, intramedullary canal reaming causes a significant release of IL-6 and an important systemic inflammatory reaction. A surgical variant technique is the introduction of the nail with no canal reaming in order to reduce the trauma produced, to simplify and speed up the process of osteosynthesis and, presumably, to reduce the systemic inflammatory response produced by the reaming procedure.The purpose of the study is the comparative evaluation between the reamed and unreamed surgical techniques in terms of increased biochemical markers of organ damage and inflammation.